Experiment on low-temperature irradiation of fluorinated detonation nanodiamond powder in the WWR-K reactor: conditions and initial characterisation of samples - Turlybekuly, K.; Aitkulov, М.Т.; Bugybay, Ж.Т.; Askerbekov, С.К.; Shaimerdenov, А.А. (Recent Contributions to Physics, 2024)
Fluorine-doped detonation nanodiamond (DND) powders are considered as a new class of neutron reflectors and can significantly improve the performance of very cold and ultracold neutron sources, which in turn will lead to new types of experiments at a qualitative level. These improvements are achieved due to such properties of DND as high diffusion and quasi-mirror reflection. The high reflectivity improves the neutron delivery efficiency and, consequently, the neutron fluxes at neutron facilities. On this basis, fluorinated DNDs are considered as a potential neutron reflector material for the designed very cold and ultracold neutron source at the WWR-K reactor. However, to date, experimental data on the behaviour of fluorinated DND in the neutron field are insufficient, and therefore, in order to study the radiation resistance of DND at the WWR-K reactor, work has been started on their irradiation and further study. For this purpose, an optimal irradiation capsule design was developed and comprehensive calculations were performed to justify the conditions and limits of reactor irradiation. This paper describes the irradiated samples and reactor experiment, the methodology and conditions for irradiating the samples, and the results of their initial characterisation after irradiation.